Family Conflict in Edward Albee’s Selected Dramas - Florida Cita Dewi Sahadun; Dahlia D. Moelier; Asyrafunnisa Asyrafunnisa (Fakultas Sastra, Universitas Bosowa, 2022)
This research aimed to identify the kinds o family conflict that appear in Edward Albee’s dramas and to know the causes and impacts of the dramas using theory of family conflict by Ursula Lehr and descriptive qualitative method. In The Sand box drama the types of family conflict are conflict with own parents, conflict with own children, conflict with husband/wife, and self-conflict. Other causes were because mommy’s selfish characteristic and always wanted to be a dominant person, while grandma was experiencing her second childhood phase. The impacts of The Sandbox drama are the fight between the characters in the drama and the loss of harmonization in the family. In who’s Afraid of Virginia Woolf? Drama, there are conflicts with other people, conflict with husband/wife, and self-conflict. The main causes were Martha and George as a marriage couple that always wanted to drop down on and insulted each other. The impacts are the loss of harmonization in the family, another couple (Nick and Honey) got into their problem fought to each other.